Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1182/bloodadvances.2021006416
|View full text |Cite
|
Sign up to set email alerts
|

Complement gene variant effect on relapse of complement-mediated thrombotic microangiopathy after eculizumab cessation

Abstract: Eculizumab is effective for complement-mediated thrombotic microangiopathy (CM-TMA), also known as atypical hemolytic uremic syndrome. Although lifelong therapy had been suggested, discontinuation does not universally lead to relapse. Comprehensive data evaluating risk factors for recurrence following discontinuation is limited. Our aim was to systematically review available literature assessing the role of complement genetic variants in this setting. Reports on CM-TMA and eculizumab withdrawal published befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Regardless of the above considerations, the new study, along with the previously published retrospective and prospective studies, 6 , 7 , 8 , 9 , S1-S4 show that even in the high-risk group of aHUS patients with pathogenic or likely pathogenic complement gene variants, 50% to 75% of patients will not relapse.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…Regardless of the above considerations, the new study, along with the previously published retrospective and prospective studies, 6 , 7 , 8 , 9 , S1-S4 show that even in the high-risk group of aHUS patients with pathogenic or likely pathogenic complement gene variants, 50% to 75% of patients will not relapse.…”
mentioning
confidence: 81%
“…However, the risk of potentially fatal meningococcal infections, the need for repeated intravenous infusions, and the extremely high cost of the drug have provided the urgent need to find ways to discontinue treatment after achieving stable clinical remission. 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies and a systematic review of the literature demonstrated eculizumab discontinuation may be safe in those who achieved hematologic remission with stable kidney function for at least 3-6 months, based on using a monitoring protocol and absence of specific complement gene variants. [115][116][117] In 2019, ravulizumab, a long-acting version of eculizumab, was approved for CM-HUS, which extended the maintenance dosing to every 8 weeks. 118 In the pivotal trial that led to its approval, eight patients developed CM-HUS postpartum.…”
Section: Management Of Complement-mediated Hemolytic-uremic Syndrome ...mentioning
confidence: 99%